2015
DOI: 10.1513/annalsats.201409-415oc
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics of l-Carnitine Treatment Response Phenotypes in Patients with Septic Shock

Abstract: The results of this preliminary study, which were not readily apparent from the parent clinical trial, show a unique metabolite profile of l-carnitine responders and introduce pharmacometabolomics as a viable strategy for informing l-carnitine responsiveness. The approach taken in this study represents a concrete example for the application of precision medicine to sepsis therapeutics that warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 46 publications
2
83
0
Order By: Relevance
“…In addition, a major logistical challenge in studying critical ill patients is their unscheduled presentation into relatively poorly controlled areas of the health care systems (e.g., the emergency department, the operating room, the ICU), which may contribute to delays, and technical variation inherent in sample handling and processing even in a clinical research setting. Nevertheless, metabolomics holds promise to inform of underlying etiology and may be a more sensitive gauge of illness severity and outcome than traditional biomarkers (e.g., SOFA scores) (17). This makes the implications of our findings particularly relevant to sepsis because the employment of sound metabolomics approaches are critical for the generation of reliable metabolomics data, though these findings are also likely to be relevant in any number of disease states notable for alterations in blood rheology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a major logistical challenge in studying critical ill patients is their unscheduled presentation into relatively poorly controlled areas of the health care systems (e.g., the emergency department, the operating room, the ICU), which may contribute to delays, and technical variation inherent in sample handling and processing even in a clinical research setting. Nevertheless, metabolomics holds promise to inform of underlying etiology and may be a more sensitive gauge of illness severity and outcome than traditional biomarkers (e.g., SOFA scores) (17). This makes the implications of our findings particularly relevant to sepsis because the employment of sound metabolomics approaches are critical for the generation of reliable metabolomics data, though these findings are also likely to be relevant in any number of disease states notable for alterations in blood rheology.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of assay, frozen samples were thawed on ice and macromolecules were removed by the addition of methanol:chloroform (1:1) as previously described (17). Following extraction, the resulting aqueous phase of each sample was assayed by 1 H-NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together with the fact that sepsis, as mentioned above, is a global health concern, this underlines the significance of metabolomics for public health. More specifically, by complementing other “-omics” technologies, employment of metabolomics has the potential to radically transform the research and clinical landscape in sepsis by enabling effective risk stratification and diagnosis [100], prognosis [101], and, with pharmacometabolomics, even targeted therapeutic approaches [102]. …”
Section: Impact On Public Healthmentioning
confidence: 99%
“…Puskarich et al [73] used 500 MHz 1 H NMR of pre-dose serum samples to show that lower baseline blood serum levels of 3-hydroxybutyrate (p < 0.001), acetoacetate (p < 0.001) and 3-hydroxyisovalerate (p < 0.001) were significantly associated with survival for septic shock patients on L-carnitine therapy (4 g bolus followed by 8 g infusion over 12 hours). The 31 patients were randomised between placebo (n = 15) and drug treatment (n = 16).…”
Section: Prediction Of Drug Efficacy Studiesmentioning
confidence: 99%
“…It is striking that pharmacometabonomics approaches are now being used to predict drug efficacy in situations that are literally life-and-death, such as the report by Puskarich et al [73] involving septic shock patients on L-carnitine therapy. Many of the studies reported are early stage and exploratory, rather than large-scale clinical trials, and many of the studies will require validation in larger cohorts of subjects.…”
Section: Conclusion and The Future For Pharmacometabonomicsmentioning
confidence: 99%